On the extraction of the power-law parts of probability density functions in star-forming clouds - Veltchev, Todor V.; Girichidis, Philipp; Donkov, Sava; Schneider, Nicola; Stanchev, Orlin; Marinkova, Lyubov; Seifried, Daniel; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2019)
We present a new approach to extract the power-law part of a density/column-density probability density function (ρ-pdf/N-pdf) in star-forming clouds
Gesehen am 18.12.2019